Collateral damage - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries, 2023)
Ali Reynolds tries to figure out who was the real target and who was the collateral damage after her husband is forced off the road in an airport limo while preparing to fly to a ransomware conference in London.